The nexus between structural capital efficiency and agency costs: evidence from listed non-financial firms in Nigeria (Journal of Economic Research & Business Administration, 2021)
The study investigated the nexus between structural capital efficiency and agency conflicts usingsample of sixty-six (66) non-financial firms listed on the Nigerian Stock Exchange between 2010 and2019. These 660 firm-year observations were extracted from the annual reports of the sample firms forvarious years. Agency costs is proxy with asset turnover rate and operating expense ratio as alternativemeasure for robustness analysis. Structural capital efficiency was obtained following Pulic (2000) estimationof value-added intellectual capital coefficient. Descriptive statistics tools of mean and standarddeviation as well as bi variate tool of correlation coefficients were used for preliminary analysis of thestudy. The hypotheses were tested using panel feasible generalized least square regression. The results ofthe analysis reveal that structural capital efficiency has significant positive impact on asset turnover ratewhile it has significant negative impact on operating expense ratio implying that results obtained are robustto alternative proxy for agency costs. It is therefore recommended that the management who wish tosatisfy the interest of their principal can leverage on the efficiency of their structural capital to achieve thegoal. In addition, the shareholders should monitor the efficiency of structural capital in their subscribedfirms since it automatically helps to limit the agency problem. Also, potential investors should considerthe efficiency of the structural capital within a firm in making their investment decisions.Key words: agency costs, agent, non-financial firms, principal, structural capital efficiency.